Evaluation of hearing levels in Crimean-Congo hemorrhagic fever with audiological and electrophysiological tests (Annals of Medical Research, 2024)
Aim: Crimean-Congo Hemorrhagic Fever (CCHF) is a tick-borne viral disease, and Sensorineural Hearing Loss (SNHL) arises from pathologies in the cochlea or retrocochlear pathways. Viral infections, including Crimean-Congo hemorrhagic fever are considered possible etiological factors for Sensorineural hearing loss, as endothelial damage in Crimean-Congo hemorrhagic fever may impair inner ear blood flow. This study aimed to differentiate between cochlear and retrocochlear hearing loss in patients with Crimean-Congo hemorrhagic fever and assess the reliability of Auditory Steady-State Response (ASSR) testing by comparing its results with pure-tone audiometry.Materials and Methods: The study included 30 Crimean-Congo femorrhagic fever patients (Group CCHF) and 30 healthy controls (Group C). Hearing measurements were conducted using pure tone audiometry, otoacoustic emissions, tympanometry, and Auditory steady-state response before the patients’ discharge. Data were analyzed using SPSS 22.0.Results: The results showed no significant difference in audiometric thresholds between the right and left ears of Group CCHF at various frequencies. However, Auditory steady-state response results at 1000, 2000, and 4000 Hz in the right ear and at all tested frequencies in the left ear revealed significant differences between groups (p
Keywords: Crimean-Congo hemorrhagic fever; Audiometry; Otoacoustic emissions; Tympanometry; Auditory steady state response; Hearing loss